Energy Storage in Supercapacitors: Focus on Tannin-Derived Carbon Electrodes - Castro-Gutiérrez, Jimena; Celzard, Alain; Fierro, Vanessa (Frontiers in Materials, 2020)
Supercapacitors (SCs) are energy storage devices that bridge the gap between batteries and conventional capacitors. They can store more energy than capacitors and supply it at higher power outputs than batteries. These features, combined with high cyclability and long-term stability, make SCs attractive devices for energy storage. SCs are already present in many applications, either in combination with other energy storage devices (mainly batteries), or as autonomous energy sources. Porous carbons are presently used in the electrodes of commercial SCs due to their high surface area and their good conductivity. However, new porous materials are continuously being developed. Herein, an outline of the principles of the energy storage mechanism in SCs is presented as a guide to illustrate the research on porous carbons materials for SC applications. Indeed, an overview of these carbons and their synthesis methods is also presented. In the context of an urgent need to progress towards the development of environmentally friendly technologies and methods, the final part of this review focuses on the studies carried out using biosourced carbon precursors, such as tannins, which are natural polyphenolic molecules. In particular, mimosa tannin-derived carbon materials with controlled micro- and mesoporosity can be produced by methods with lower environmental impact and lower health and safety risks because crosslinkers are not needed to produce resins.